2018
DOI: 10.1016/j.resp.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of metabolic alkalosis on the ventilatory response in healthy subjects

Abstract: A B S T R A C TBackground: Patients with acute respiratory failure may develop respiratory acidosis. Metabolic compensation by bicarbonate production or retention results in posthypercapnic alkalosis with an increased arterial bicarbonate concentration. The hypothesis of this study was that elevated plasma bicarbonate levels decrease respiratory drive and minute ventilation. Methods: In an intervention study in 10 healthy subjects the ventilatory response using a hypercapnic ventilatory response (HCVR) test wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 29 publications
0
9
1
1
Order By: Relevance
“…[13] is is because of a serum bicarbonate level 2 mEq/L more than others, in which metabolic alkalosis could also affect the respiratory drive and minute ventilation. [14] e result of this study is not supported by DOSE-AHF study that shows diuretic benefits on curing organ system dysfunction caused by fluid overload (including cerebral edema, pulmonary edema, myocardial edema, hepatic congestion, renal interstitial edema, and intestinal edema). [8] However, previous research supports the result of the study, stating that diuretic usage causes acute kidney injury and increases the mortality of patients with 1.68 odd ratios.…”
Section: Discussioncontrasting
confidence: 71%
“…[13] is is because of a serum bicarbonate level 2 mEq/L more than others, in which metabolic alkalosis could also affect the respiratory drive and minute ventilation. [14] e result of this study is not supported by DOSE-AHF study that shows diuretic benefits on curing organ system dysfunction caused by fluid overload (including cerebral edema, pulmonary edema, myocardial edema, hepatic congestion, renal interstitial edema, and intestinal edema). [8] However, previous research supports the result of the study, stating that diuretic usage causes acute kidney injury and increases the mortality of patients with 1.68 odd ratios.…”
Section: Discussioncontrasting
confidence: 71%
“…All organs including the respiratory muscles have a basal metabolic supply, whose impairment through metabolic disorders (hypo/hyperthyroidism, adrenal insufficiency, hyperglycaemia), electrolyte disorders (hyperkalaemia, magnesium and phosphate deficiencies), albumin deficiency, or exogenous endocrine factors such as glucocorticoidsteroid therapy, can lead to functional disorders [17, 45, 121]. Furthermore, metabolic alkalosis can promote weaning failure by attenuating respiratory drive with compensatory hypercapnia [122, 123]. Similarly, metabolic acidosis should also be considered as a cause of prolonged weaning, since it places a further strain on the already overloaded respiratory pump through ventilatory compensation [124].…”
Section: Pathophysiology Of Weaning Failurementioning
confidence: 99%
“…41 Since patients receiving diuretics had a serum bicarbonate level of 2 mEq/L above others, and metabolic alkalosis can reduce the neural respiratory drive and minute ventilation, the authors argued that the metabolic side effect of diuretics could contribute to the observed mechanical ventilation weaning difficulties. 41,42 In the face of positive fluid balance during the de-escalation phase of sepsis management, one might consider earlier application of renal replacement therapy (RRT), especially in those patients with more severe volume overload, progressive metabolic alkalosis with diuretic use, suboptimal diuretic response or diuretic refractoriness, and development of oliguric AKI. In light of evidence on the detrimental impact of RRT use for treatment of sepsis (through clearance of inflammatory mediators and cytokines), 43 RRT should be considered only if indicated for optimization of volume status or treatment of azotemia.…”
Section: Active Fluid Removalmentioning
confidence: 99%